Towards Energy-Efficient Residential Buildings In Jeddah, Saudi Arabia - Ahmed Felimban (A+BE: Architecture and the Built Environment, 2024)
The thesis explores energy retrofitting options for enhancing the energy efficiency of residential buildings in Jeddah, Saudi Arabia. It identifies and validates cost-effective energy retrofit schemes that have the potential for energy savings. The thesis also assesses the feasibility of energy retrofitting scenarios for building envelopes and their impact on reducing energy consumption, improving thermal comfort, and mitigating the environmental impact of buildings. The results of this research can guide architects and decision-makers on energy-saving measures for residential buildings in Saudi Arabia, with Jeddah serving as a representative case study.